SITE SELECTION FOR CLINICAL RESEARCH IN INDIA - Bangera, Sudhakar; Ms, Latha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
For biopharmaceutical companies, in order to prevent excessive expenditure, completing a clinical trial on time is a very important factor. Selection of the right study site(s), trained investigators and site coordination team are key factors in determining timely completion of the study. There are few criteria (study and sponsor specific) that have to be met by sites to allow them to qualify and participate in the study. By adhering to these, the value of the sponsor's time and money can be enhanced. Though site selection in India is similar to that in other countries, there are a few cultural differences that the sponsors should be aware of. Based on our experiences, we provide guidance here to address practical issues that may be encountered while selecting a site and an investigator in India. Study sites in India have the potential to become world-class study sites, but require an infrastructure and proper training. With an available patient pool along with an unmet health need, Indian sites offer an attractive alternative to their foreign counterparts. Keywords: Clinical trial, Infrastructure, Investigator, Site selection, Training.